DRIVING EMPLOYEE PERFORMANCE: COMPENSATION, MOTIVATION, AND WORK FACILITIES AS KEY LEVERS - Evinta Amalia Nurhidayah; Sinar Hubtriyan Ade; Sukarsono Sukarsono (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
Abstract. This study aims to examine the effect of compensation, motivation, and work facilities on employee performance at the Agriculture and Food Office of Kendal Regency. Employee performance is a key determinant of organizational success, yet prior studies show inconsistent findings regarding the influence of these variables. This research uses a quantitative approach with a saturated sampling technique involving 35 employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results show that compensation, motivation, and work facilities each have a positive and significant effect on employee performance, both partially and simultaneously, with the three variables explaining 60.1% of the variance in performance. These findings confirm that adequate compensation, strong motivation, and supportive work facilities are essential for sustaining high employee performance and provide practical implications for public sector human resource management.